The Strategic Management Practices in Enhancing Administrative Staff Performance - Andriani Andriani; Siti Raudhatul Jannah; Summiyani Summiyani (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
This study aims to analyze the implementation of strategic management by the administrative head in improving the performance of administrative staff at MAN 2 Muaro Jambi. The study employed a qualitative approach using a case study design to explore managerial practices, organizational coordination, and administrative performance improvement within the madrasah environment. Data were collected through observations, semi-structured interviews, and documentation involving the administrative head, administrative staff, and institutional documents. Data analysis was conducted using the interactive model of data reduction, data display, and conclusion drawing. The findings revealed that the implementation of strategic management contributed positively to improving administrative staff performance through clear job descriptions, routine supervision and evaluation, digital administrative systems, and continuous professional development programs. The integration of digital administration improved work efficiency, strengthened administrative accountability, and accelerated document management processes. The study also identified several challenges, including limited technological competence among some staff members and inadequate administrative facilities. However, opportunities such as government support, digital transformation programs, and training activities supported organizational improvement within the institution. Overall, this study highlights that strategic management implementation plays an important role in improving organizational effectiveness, employee discipline, and administrative service quality within Islamic educational institutions.